Antioxidant Activity and Flavones Compounds Contents of Tartary Buckwheat Seedlings Extract - Bin Xiong, Hua; Hong Liu, Man; Hong Chen, Ming; Hui Dai, Jian; Tao Gao, Yun (Asian Journal of Chemistry, 2013)
Flavonoids extract of tartary buckwheat seedlings was prepared by ultrasound-assisted extraction and AB-8 macroporous resin purification. High performance liquid chromatography analysis showed that flavones compounds such as rutin, quercetin and kaempfenol were the primary characteristic compounds in the flavonoids extract. The flavonoids extract and flavone compounds of tartary buckwheat seedlings exhibited strong free radical scavenging activity, especially against hydroxyl radical and DPPH radical, along with superoxide radical, which could be related to the reducing power and metal iron chelating activity of flavone compounds in tartary buckwheat seedlings. The radical scavenging activity and lipid peroxidation inhibiting activity of the flavone compounds decreased in the same order as following: quercetin > rutin > kaempfenol. This work has gathered experimental evidences on the great potential of tartary buckwheat seedlings as an easily accessible health food, natured antioxidant for its high content of flavonoids, low cost and very short cultivated period. This work has gathered experimental evidences on the great potential of tartary buckwheat seedlings as an easily accessible health food, natured antioxidant.